Analysis Of Differences The Quality Randang Eel With The Handling Technique Grilled And Fried Eel - Adrinelvita Adrinelvita; Elida Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The study aimed to analyze the differences in the quality of rendang eel with the technique of handling grilled and fried eels. The type of research conducted is quantitative research with experiment methods, namely conducting direct experiments on the manufacture of eel rendang with different handling techniques. The study used a completely randomized design (CRD) with 3 replications. The data used is primary data obtained directly from 3 expert panelists who provide answers to a questionnaire (organoleptic test format) about the quality of eel randang with different handling techniques. The data obtained are tabulated into tabular form and analyzed to see the difference between the two treatments with (t test). If the data analysis shows tcount ttable then Ha is accepted and if tcount ttable then H0 is accepted. Based on the results of data analysis of eel rendang using grilled and fried eel handling techniques, the results of data analysis showed that there was no significant difference between X1 and X2 treatments on the quality of eel rendang which stated that H0 was accepted. Overall, with the average tabulation of data, the best results from the two variables are in the fried eel handling technique (X2). For further research, it is recommended to use the technique of handling rendang eel by frying because the value of color, aroma and taste quality is superior to the technique of handling burnt eel (X1).